Strona 1 z 1

równania

: 25 sty 2007, o 13:44
autor: marcin.p
Rozwiąż równania:
a)x^6-64=0
b)(x�+x)^4-1=0
c)2x^5+3x^4-2x-3=0
d)5x^5+4x^4-5x-4=0

równania

: 25 sty 2007, o 14:10
autor: grzegorz87
c) \(\displaystyle{ 2x^{5}+3x^{4}-2x-3=0}\)
\(\displaystyle{ x^{4}(2x+3)-(2x+3)=0}\)
\(\displaystyle{ (2x+3)(x^{4}-1)=0}\)
\(\displaystyle{ (2x+3)(x^{2}-1)(x^{2}+1)=0}\)
\(\displaystyle{ (2x+3)(x-1)(x+1)(x^{2}+1)=0}\)

[ Dodano: 25 Styczeń 2007, 14:12 ]
d) ten sam sposób

równania

: 25 sty 2007, o 14:17
autor: Lorek
\(\displaystyle{ x^6-64=0\\(x^3-8)(x^3+8)=0\\(x-2)(x^2+2x+4)(x+2)(x^2-2x+4)=0}\)
2 kwadratowe nie mają pierwiastków
2.
\(\displaystyle{ (x^2+x)^4-1=0

\([(x^2+x)^2-1][(x^2+x)^2+1]=0\\(x^2+x-1)(x^2+x+1)[(x^2+x)^2+1]=0}\)

tu tylko coś z 1 nawiasu policzysz.